Las técnicas grafo plásticas y la motricidad fina en niños de preparatoria de la Unidad educativa Nambacola del cantón Gonzanamá, periodo académico 2021-2022. - Escaleras Jaramillo, Vanessa De Los Angeles (2022)
The development of fine motor skills is fundamental in children from zero to six years old, since it requires particular and systematic movements where small muscles of infants intervene, such as hands and fingers, making it easier to make the digital clamp and achieve the oculus-manual coordination. Therefore, the general objective of this work was to determine how plastic graph techniques enhance fine motor skills in high school children of the Nambacola Educational Unit of canton Gonzanamá, academic period 2021-2022; for its achievement the quantitative research approach was used, with a descriptive scope and a quasi-experimental design, in addition, the following methods were used: inductive-deductive and analytical- synthetic. Likewise, it was worked with a population of 15 children, from which it was not possible to extract a sample because the group was small, they were applied an initial evaluation using the fine motor checklist, where it was possible to show that 27% of the children had a good influence of fine motor skills. After the implementation of the didactic guide called "I have fun playing with my little hands", which was based on the deficiencies found, it was noted that 46% improved their fine motor skills, that is, in the post-test they reached 73%. What led to the conclusion that the use of plastic graph techniques in the development of fine motor skills in high school children is a good option; because these techniques can enhance the motor development of children as well as helping them to gain independence and security in the activities they carry out in their daily life. Keywords: Didactic guide, plastic graph, fine motor skills, digital clamp, preparatory, techniques.